Cyclodextrin Nanoparticles Bearing 8‐Hydroxyquinoline Ligands as Multifunctional Biomaterials. Issue 18 (8th March 2017) - Oliveri, Valentina; Bellia, Francesco; Vecchio, Graziella
Abstract: Cyclodextrins are used as building blocks for the development of a host of polymeric biomaterials. The cyclodextrin polymers have found numerous applications as they exhibit unique features such as mechanical properties, stimuli responsiveness and drug loading ability. Notwithstanding the abundance of cyclodextrin polymers studied, metal‐chelating polymers based on cyclodextrins have been poorly explored. Herein we report the synthesis and the characterization of the first metal‐chelating β‐cyclodextrin polymer bearing 8‐hydroxyquinoline ligands. The metal ions (Cu 2+ or Zn 2+ ) can modulate the assembly of the polymer nanoparticles. Moreover, the protective activity of the new chelating polymer against self‐ and metal‐induced Aβ aggregation and free radical species are significantly higher than those of the parent compounds. These synergistic effects suggest that the incorporation of hydroxyquinoline moieties into a soluble β‐cyclodextrin polymer could represent a promising strategy to design multifunctional biomaterials. Abstract : Going metallic : The metal ions (Cu 2+ or Zn 2+ ) can modulate the assembly of the novel metal‐chelating β‐cyclodextrin polymer bearing 8‐hydroxyquinoline ligands. The synergistic effect of cyclodextrins and quinolines determines the high inhibitory modulation toward self‐ and metal‐induced Aβ aggregation.